Examination of surgical and conservative treatment effects on depression of patients with moderate carpal tunnel syndrome - Güvenç, Kenan; İlik, Mustafa Kemal; İlik, Faik; Gönen, Murat; Kayhan, Fatih (The European Research Journal, 2019)
Objective: The aim of this study is to examine the outcomes of conservative and surgical treatments of patients with carpal tunnel syndrome as well as the effects of these two treatment options on depressive symptoms of these patients. Methods: A case-control study carried out from June 2015 to Fabruary 2016 and 111 moderate moderate carpal tunnel syndrome patients were included in the study whose diagnosis was confirmed by electroneuromyography (ENMG). The 78 of the patients had surgical treatment and 33 of them, who did not accept the surgery, received steroids via injection and splinting technique was performed for 8 weeks. Boston Carpal Tunnel Questionnaire, quick disabilities of the arm, shoulder and hand score and Beck Depression Invertory scales were applied six months before and after treatments. Results: It was detected that pain functional assessment scores and Beck depression scores significantly recovered the disease in patients who had surgical treatment compared to ones who had the conservative treatment. Conclusions: It can be concluded that surgical treatment plays a more active role in the recovery of depressive symptoms in patients with moderate carpal tunnel syndrome.